Development of Ethno-Stem E-Modules Integrated with Batik Situbondo to Improve Students' Creative Thinking Skills in Junior High School Science Learning - Muliana, Siti; Ahmad, Nur; Rusdianto, Rusdianto (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
Developing interactive and contextual learning media is crucial in enhancing 21st-century skills, particularly creative thinking. However, the facts show that many students still have difficulty developing these skills, especially in science learning, which is often considered abstract and complex. This study aims to develop and analyze the effectiveness of the Etno-STEM E-Module, which integrates science concepts with local culture through Situbondo batik to enhance students’ creative thinking skills. This research employs the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Effectiveness was measured using pre-test and post-test results analyzed with the N-Gain Score. The trial was conducted on seventh-grade students at SMP Negeri 2 Panji, Situbondo. The results indicate that the e-module has a very high level of validity, with an average score of 92%, is considered practical with a score of 95,2%, and is effective in improving students’ creative thinking skills, achieving an N-Gain score of 0.63 in the medium category. The implications of this research suggest that integrating local culture into STEM-based learning can be an innovative solution to enhance students’ creative thinking skills. Therefore, this e-module has the potential to be applied in science education across various educational contexts.